2013
DOI: 10.1007/s10532-013-9673-y
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of microcystin-LR and-RR by a novel microcystin-degrading bacterium isolated from Lake Taihu

Abstract: Microcystin-LR (MC-LR) and microcystin-RR (MC-RR) are the two most common microcystins (MCs) present in fresh water posing a direct threat to public health because of their hepatotoxicity. A novel MC-degrading bacterium designated MC-LTH1 capable of degrading MC-LR and -RR was isolated, and the degradation rates and mechanisms of MC-LR and -RR for this bacterium were investigated. The bacterium was identified as Bordetella sp. and shown to possess a homologous mlrA gene responsible for degrading MCs. To the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 30 publications
3
51
1
Order By: Relevance
“…However, when it was present as the sole microcystin in the same media it was completely degraded in 24 days. These results are consistent with findings from Yang et al (2014) who investigated the biodegradation of MCLR and MCRR by a new microcystin-degrading bacterium. They reported that the isolate MC-LTH1 was able to degrade MCLR and MCRR more quickly when they were not simultaneously present.…”
Section: Biodegradation Of Individual Microcystins In Filtered Lake Wsupporting
confidence: 92%
“…However, when it was present as the sole microcystin in the same media it was completely degraded in 24 days. These results are consistent with findings from Yang et al (2014) who investigated the biodegradation of MCLR and MCRR by a new microcystin-degrading bacterium. They reported that the isolate MC-LTH1 was able to degrade MCLR and MCRR more quickly when they were not simultaneously present.…”
Section: Biodegradation Of Individual Microcystins In Filtered Lake Wsupporting
confidence: 92%
“…These suggested that MC-biodegradation was accompanied with the increase in MCdegrader abundance among overall bacterial community, and the degree of MC-degrader growth was positively correlated with total MCs amount. These data can be comparable to Yang et al (2013), who also showed that the MC-degrader density increased during MCs biodegradation in pure isolate culture and multiple MCs variants (MCLR plus MCRR) may act additively to promote the MC-degrader abundance. Thus, it can be inferred that all of MCLR, MCRR and MCYR were used as carbon and nitrogen sources for MCdegrader growth.…”
Section: Separate and Simultaneous Biodegradation Of Mcs With The Biosupporting
confidence: 84%
“…Although both separate and simultaneous MCs biodegradation have been widely conducted, so far few attempts were made to compare between the separate and simultaneous biodegradation of MCs. Only one example demonstrated that both MCLR and MCRR biodegradation rates decreased when both of them were simultaneously degraded (Yang et al, 2013). This study nonetheless indicated that there were no apparent differences in biodegradability between independent and simultaneous biodegradation of MCs.…”
Section: Separate and Simultaneous Biodegradation Of Mcs With The Biomentioning
confidence: 76%
“…, were fragment ions. The product ions were consistent with those in the ESI-MS spectra, Adda, which is identified as both of the anoxic [13] and aerobic degradation product [22,23] of MCLR. These results indicated that the intermediate degradation products of MCLR produced successively by ALA-1 under anaerobic condition were linearized MCLR, tetrapeptide and Adda.…”
Section: Identification Of Intermediate Degradation Productssupporting
confidence: 72%
“…and Bordetella sp. [12,22,23]. Furthermore, Adda has been detected as a degradation product of MCLR by anoxic sediment of Lake Dianchi [13].…”
Section: Identification Of Intermediate Degradation Productsmentioning
confidence: 94%